Reflexiones sobre el proyecto Auto-Demarcación y EtnoCartografía de las Tierras y Hábitats Jodï y Eñepa - Stanford Zent; Egleé L. Zent; Lucas Juae Mölö; Pablo Chonokó (Revue d'ethnoécologie)
This paper reflects on practical and conceptual lessons acquired as a result of our participation in a project of self-demarcation of indigenous lands in Venezuela. The project was based on a collaboration between academics from the Venezuelan Institute for Scientific Research (IVIC) and local communities of the Jodï and Eñepa ethnic groups. The goal was to prepare maps of community lands and compile all of the documentation required to petition the Venezuelan State for the land title. The first point proves the importance of alliances among local communities and external actors (such as academy-trained researchers) in order to navigate the complicated route of ethno-cartographic documentation and bureaucratic motions that leads from the theoretical recognition of territorial rights to the real and effective tenure over the land. Such collaborations imply the integration of complementary capabilities but also the mutual understanding of dissimilar perceptions and interests. In the second place, we analyze the ambiguity of the State in regards to Indian land rights recognition throughout the Bolivarian constitutional period, as reflected in various contradictions between written laws and legal practices, the separate actions and attitudes of different government agents at regional and national levels, the inconsistencies in the institutional authorities and application of norms established to promote the demarcation process, the legal lacunae or recurrent changes in the rules regarding the petition of land rights recognition, among other aspects that have impeded reaching the final goal of indigenous land demarcations: obtaining legal title or ownership rights over their lands. Third, the multiple realities of the map are evidenced by spatial-temporal polysemy, which have forced us to recognize the different ways of perceiving and experiencing space and time among non-western peoples, for example internalized in daily life yet externalized in symbolic representations at the same time. Lastly, we explore how indigenous territories can contribute to biocultural conservation policy. We conclude with the observation that collaborative projects geared toward community mapping and land demarcation, in which local community members and academic researchers participate actively in tandem, offer a promising venue for advancing ethnoecological research.